KINERJA APARATUR SIPIL NEGARA DALAM PENGURUSAN SERTIFIKAT TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR PERTANAHAN KABUPATEN MINAHASA - Aube, Oldi; Pratiknjo, Maria Heny; Tampongangoy, Deysi Livy Natalia (Sam Ratulangi University, 2022)
This study aims to determine and analyze the performance of state civil servants in obtaining land certificates through the Complete Systematic Land Registration Program (PTSL) at the Minahasa Regency Land Office. This research method uses a qualitative descriptive method, with research indicators consisting of quality, quantity, use of time and work commitment. Data analysis uses steps, namely data reduction, data presentation, levers or withdrawals, and data conclusions. The results showed that the performance of the state civil apparatus who took care of the land through the Complete Systematic Land Registration Program (PTSL) at the Minahasa Regency Land Office, in carrying out their duties and functions on the number of employees where employees who run PTSL were the same employees in carrying out management work. with independent and cross-sector categories, so that it can be said to be included in the unfavorable criteria.